PEMBELAJARAN BAHASA BALI KONTEKSTUAL PADA PEMBELAJAR MUDA; STUDI KASUS DI TK NEGERI MUNDUK BESTALA - Komang Puteri Yadnya Diari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Language learning has developed along with the development of linguistics theory. Currently, language learning emphasizes the use language in natural setting instead of focusing on linguistics feature such as grammar and vocabulary. Language learning currently also emphasizes the communicative competence of students. Communicative competence is the ability to communicate directly to exchange ideas, thoughts, and feelings. The paradigm shift in language theory directly changes the language learning paradigm. This paradigm includes methods, approaches and teaching strategies. One approach to language learning that emphasizes communicative competence is contextualized language instruction. Contextualized language instruction is a learning approach that believes that language is closely related to context. The purpose of writing this paper is to look at the syllabus and lesson plans for kindergarten that apply contextualized language instruction in Balinese language lessons. Keywords: Balinese, Contextualized Instruction, Young Learners